IMPLEMENTING ALTERNATIVE DISPUTE RESOLUTION ON WAQF LAND CONFLICT OF ISLAMIC BOARDING SCHOOLS RAUDHATUL JADID AL JAZURI, MEUKEK DISTRICT, SOUTH ACEH - Andhika Djesi Fernanda; Delfi Suganda (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This article discusses a dispute over waqf land at the Raudhatul Jadid Al Jazuri Islamic boarding school in Meukek District, South Aceh Regency. A plot of land measuring 25 x 94 metres was donated by Lukman in 2005 and has been used for the boarding school's purposes. However, in recent years, a conflict has emerged due to differing views among the parties involved regarding the status and use of the land. This article highlights efforts to resolve the dispute so that the endowed land can continue to be used in accordance with its original vision. The author collected data from the field or within the community as part of the field research conducted for this study. Additionally, a qualitative approach was used, which is a research and understanding process based on methodologies that delve into social phenomena and human issues. Primary data was obtained through in-depth interviews, while secondary data was obtained from relevant literature surveys. The study's findings indicate that conflicting understandings about the nature of waqf land are the root cause of land conflicts at the Raudhatul Jadid Al Jazuri Islamic boarding school. Waqf land is considered permanent under Islamic law and Indonesian regulations. Any resolution related to waqf land must comply with applicable requirements.